Hepatic Involvement in Aicardi-Goutières Syndrome - Gavazzi, Francesco; Cross, Zachary M.; Woidill, Sarah; McMann, Joseph M.; Rand, Elizabeth B.; Takanohashi, Asako; Ulrick, Nicole; Shults, Justine; Vanderver, Adeline L.; Adang, Laura (Neuropediatrics, 2021)
Aicardi-Goutières syndrome (AGS) is a monogenic type-I interferonopathy that results in neurologic injury. The systemic impact of sustained interferon activation is less well characterized. Liver inflammation is known to be associated with the neonatal form of AGS, but the incidence of AGS-related hepatitis across lifespan is unknown.We compared natural history data including liver enzyme levels with markers of inflammation, (liver-specific autoantibodies and interferon signaling gene expression[ISG] scores). Liver enzymes were classified as normal or elevated by the fold increase over the upper limit of normal (ULN). The highest increases were designated as hepatitis, defined as aspartate-aminotransferase or alanine-aminotransferase threefold ULN, or gamma-glutamyl transferase 2.5-fold ULN. A larger cohort was used to further characterize the longitudinal incidence of liver abnormalities and the association with age and genotype.Across the AGS cohort (n = 102), elevated liver enzymes were identified in 76 individuals (74.5%) with abnormalities at a level consistent with hepatitis in 29 individuals (28.4%). SAMHD1 mutations were less likely to be associated with hepatitis (log-rank test; p = 0.011). Hepatitis was associated with early-onset disease and microcephaly (log-rank test; microcephaly p = 0.0401, age onset p = 0.0355). While most subjects (n = 20/33) were found to have liver-specific autoantibodies, there was no association between the presence of autoantibodies or ISG scores with hepatitis-level enzyme elevations.In conclusion, all genotypes of AGS are associated with transient elevations of liver enzymes and the presence of liver-associated autoantibodies. This adds to our growing understanding of the systemic pathology AGS.
Keywords: Aicardi-Goutières syndrome; liver; ISGs